Tinjauan Literatur: Peran Teripang (Holothuria scabra) Sebagai Anti-Inflamasi - Dwinda Husna Shofiyah (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Chronic inflammation is a major contributing factor to the development of degenerative diseases such as diabetes, cancer, and cardiovascular disorders. This literature review aims to examine the anti-inflammatory potential of sea cucumber (Holothuria scabra) based on five recent experimental studies. The findings indicate that H. scabra effectively suppresses the production of pro-inflammatory mediators such as NO, iNOS, PGE₂, IL-1β, TNF-α, and IL-6, and inhibits key signaling pathways including NF-κB and JNK. Moreover, active compounds such as scabraside and holothurinoside G demonstrate the ability to inhibit KEAP1, thereby activating the Nrf2 pathway involved in cellular protection against oxidative stress. Evidence from in vivo study also shows H. scabra’s capability to reduce tissue lesions caused by inflammation. Therefore, H. scabra holds great promise as a natural anti-inflammatory agent for the prevention and treatment of chronic inflammatory conditions.